IMPLEMENTATION OF ECO-TOURISM PRINCIPLES IN SOLOP BEACH INDRAGIRI HILIR REGENCY - Fitria Dwi Sukmawati; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
Research was carried out in April 2021, with the title: Implementation of Ecotourism Principles on Solop Beach, Indragiri Hilir Regency. This study aims to find out how to apply the principles that have been carried out in the Solop Beach Ecotourism Object Area. This study uses qualitative methods to obtain primary and secondary data where data collection is done by means of interviews, observations, and documentation. Community participation, education, and conservation are the principles of ecotourism at solop beach.The results obtained from this study show that Solop Beach Ecotourism has implemented the principles of ecotourism but lacks support from external parties, namely the lack of coordination between the government and the local community.Key words : Implementation, eco- tourism principles, in Solop Beach